Mathematics in Early Education: Evaluating the Pedagogical Content Knowledge of Turkish Pre-service Preschool Teachers - Dagli, Hatice; Daglioglu, Hacer Elif; Yildiz Altan, Rukiyye; Genc Copur, Hilal (Hacettepe Univ, 2026)
This study aims to explore the pedagogical content knowledge levels of mathematics among pre-service preschool teachers in terms of various variables. The working group involved a total of 262 pre-service teachers, comprising 152 individuals in the 2nd grade and 110 in the 4th grade, studying in the preschool teaching program at four distinct state universities in Turkey. The study employed the relational survey model, utilizing Pre-service Teachers Information Form and Preschool Education Teachers' Pedagogical Content Knowledge Scale on Mathematics as data collection instruments. The findings demonstrated that pre-service teachers exhibited close to high level of pedagogical content knowledge in mathematics. The content areas in which pre-service teachers provided the most correct answers were counting, matching, and graphing, while processes were found to be particularly associated with communication and association. Preservice teachers' pedagogical content knowledge of mathematics did not differ significantly across grade levels. On analysing the content and processes separately based upon grade levels, a significant difference favouring fourth graders was identified, particularly in matching, pattern, and classification. However, no significant difference was observed in processes concerning grade levels. The participants' pedagogical content knowledge of mathematics did not significantly vary across the universities they attended.
Keywords: Preschool education; pedagogical content knowledge; mathematics; content; process